THE STRUCTURE AND LONG-TERM DYNAMICS OF THE ICE COVER IN THE LOWER REACH OF THE AMUR RIVER - A. N. Makhinov; V. I. Kim; D. V. Matveenko (Лëд и снег)
The severity of the climate in the lower reaches of the Amur River, characteristics of the river water regime, dynamics of the channel processes together with meteorological factors determine rather specific ice regime of this river. The freeze-up on the river lasts from 152 (Khabarovsk) to 185 (the city of Nikolaevsk-on-Amur) days, and by the end of winter the ice thickness reaches, on the average, 1.0–1.2 m. Three main types of the ice thickness structure are recognized according to conditions of the ice formation. The first type is much hummocky ice, consisting of the ice fragments frozen together over the entire thickness after the end of the autumn ice drift. It is widespread in channels of the largest branches of the river and is characterized by a thickness up to 2.2 m and the great quantities of terrigenous inclusions – up to 1.064 g/dm3. The second type is weakly hummocky ice comprising two layers. The upper part consists of fragments with inclusions of terrigenous particles, while the bottom one – of the homogeneous transparent ice thickness frozen during the winter. The third type is the pure homogeneous ice formed during the winter in small branches of the river. Its thickness is about 0.9–1.1 m, and the average content of terrigenous material is about 0,046 g/dm3. When compared with the climate situation of 1930–1990, the global climate warming of 1991–2013 resulted in a shift in dates of the main spring and autumn ice phenomena by 2–3 days, while the duration of the stable ice cover reduced by 3–4 days.